PENGARUH MODEL PEMBELAJARAN CPS (CREATIVE PROBLEM SOLVING) TERHADAP KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR KOGNITIF SISWA - Munisah, Munisah; Nurhidayati, Siti; Royani, Ida (Bioscientist : Jurnal Ilmiah Biologi, 2018)
The problem that happened in MTs NW Darussholihin Wassyakirin is creative thinking skill and cognitive learning result of student is still less satisfactory, proved by the value of MID semester under KKM (Criteria Completed Minimal). This is because the learning process is not effective because the use of methods or learning models that are not effective. The purpose of this research is to know the influence of CPS (Creative Problem Solving) model of creative thinking skill and students’ cognitive learning outcomes. This type of research is quasi experimental research with pretest postest control group design research design. The instrument used in this research is the observation sheet of learning implementation (RPP), test of creative thinking skill and test of cognitive learning result of the students. Data collection techniques are observations and tests, while data analysis techniques are descriptive and t-test. The results showed that the data presentation of creative thinking skills of students in the experimental class is 85.33 with very high category while the result of cognitive learning posstest students get the average value in the experimental class that is 80.83 and the control class is 78.67. The result of study posttest showed that the average learning result of the students in the experimental class and the control class were 86 and 76. Based on the t-test analysis with separated variance formula with 5% significant, student learning result obtained tcount of 2,581 and ttable value of 2.048, means tcount is greater than ttable value (2.581 > 2.048) so that (Ho) is rejected (Ha) accepted. Based on these results can be concluded that the model of learning CPS (Creative Problem Solving) effect on student cognitive learning outcomes, and average creative thinking skills achieve high categories.